(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2024)
«O beatrice» marks a turning point in Giovanni Giudici’s poetic journey, especially from the point of view of linguistic experimentation and meta-poetic reflection. Indeed, in the period coinciding with the writing of the collection, Giudici reflected onthe issue of poetic language and his own conception of the poem. This paper sets out someof Giudici’s literary and philological reflections and analyzes the most significant authorial variants, identified through survey work in the archives, in order to outline the poet’s main lines of work and shed new light on the author’s poetics and the 1972 collection.